Combined Drought and Heat Activates Protective Responses in Eucalyptus globulus That Are Not Activated When Subjected to Drought or Heat Stress Alone - Correia, Barbara; Hancock, Robert D.; Amaral, Joana; Gomez-Cadenas, Aurelio; Valledor, Luis; Pinto, Glória (Frontiers in Plant Science, 2018)
Aiming to mimic a more realistic field condition and to determine convergent and divergent responses of individual stresses in relation to their combination, we explored physiological, biochemical and metabolomic alterations after drought and heat stress imposition (alone and combined) and recovery, using a drought-tolerant Eucalyptus globulus clone. When plants were exposed to drought alone, the main responses included reduced pre-dawn water potential (Ψpd) and gas exchange. This was accompanied by increases in malondialdehyde (MDA) and total glutathione, indicative of an oxidative stress. Abscisic acid (ABA) levels increased while the content of jasmonic acid (JA) fell. Metabolic alterations included reductions in the levels of sugar phosphates accompanied by increases in starch and non-structural carbohydrates. Levels of α-glycerophosphate and shikimate were also reduced while free amino acids increased. On the other hand, heat alone triggered an increase in relative water content (RWC) and Ψpd. Photosynthetic rate and pigments were reduced accompanied by a reduction in water use efficiency (WUE). Heat induced a reduction of salicylic acid (SA) and JA content. Sugar alcohols and several amino acids were enhanced by heat treatment while starch, fructose-6-phosphate, glucose-6-phosphate and α-glycerophosphate were reduced. Contrary to what was observed under drought, heat stress activated the shikimic acid pathway. Drought-stressed plants subject to a heat shock exhibited a sharp decrease in gas exchange, Ψpd and JA, no alterations in electrolyte leakage, MDA, starch and pigments and increased glutathione pool in relation to control. Comparing this with drought stress alone, subjecting drought stressed plants to an additional heat stress alleviated Ψpd and MDA, maintained an increased glutathione pool and reduced starch content and non-structural carbohydrates. A novel response triggered by the combined stress was the accumulation of cinnamate. Regarding recovery, most of the parameters affected by each stress condition reversed after re-establishment of control growing conditions. These results highlight that the combination of drought and heat provides significant protection from more detrimental effects of drought-stressed eucalypts, confirming that combined stress alter plant metabolism in a novel manner that cannot be extrapolated by the sum of the different stresses applied individually.